2020
DOI: 10.29311/ndtps.v0i15.3590
|View full text |Cite
|
Sign up to set email alerts
|

The university campus and a sense of belonging: what do students think?

Abstract: The physical configuration of the university campus impacts upon student learning and experience, and can be used to signal institutional priorities. The extent to which campus, particularly in post 92 institutions, is designed as opposed to evolving as older buildings are repurposed or replaced is variable. Student experiences and perceptions of the campus physical space are also unclear. This study aimed to explore student perceptions using qualitative methods. Data were collected during 8 focus groups from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Respondents also identified good relationships with academic staff and the feeling that students mattered individually to staff as hallmarks of high quality HE (Dicker et al, 2017(Dicker et al, , 2018 this an important consideration in the competitive world of education provision. Rather like Ahn and Davis (2019), we have also found that there is an element of 'place' in belonging: that geographical location affects belonging in Level 3 (foundation) students (Goldring et al, 2018) and that the physical space on campus helps to develop belonging in undergraduate students (Mulrooney and Kelly, 2020b). This is unsurprising, since the nature of the physical space will influence how easily social interactions within and between staff and student groups occur.…”
Section: Introductionmentioning
confidence: 75%
“…Respondents also identified good relationships with academic staff and the feeling that students mattered individually to staff as hallmarks of high quality HE (Dicker et al, 2017(Dicker et al, , 2018 this an important consideration in the competitive world of education provision. Rather like Ahn and Davis (2019), we have also found that there is an element of 'place' in belonging: that geographical location affects belonging in Level 3 (foundation) students (Goldring et al, 2018) and that the physical space on campus helps to develop belonging in undergraduate students (Mulrooney and Kelly, 2020b). This is unsurprising, since the nature of the physical space will influence how easily social interactions within and between staff and student groups occur.…”
Section: Introductionmentioning
confidence: 75%
“…Lack of accessibility for students with disabilities was also frequently evoked in the analyzed literature, typically associated with inaccessible buildings, websites, learning management systems, and virtual resources, lack of lifts and other adaptive and supportive equipment, and the absence of interpreters or signage in braille (Morina, et al, 2016;van Jaarsveldt & Ndeya-Ndereya, 2015). For many students with disabilities, accessibility goes beyond built structures and includes a broader conception of a variety of environments, including social and attitudinal aspects, outdoor spaces, transportation, and communication (Bencicni & Arenghi, 2018;Mulrooney & Kelly, 2020).…”
Section: Barriers To Inclusion and Belongingmentioning
confidence: 99%
“…Also critical to a sense of belonging are supplementary infrastructure, accessible and inviting spaces, inclusive policies and procedures, and student support services which collectively form the foundation upon which socialization occurs. Universities and colleges are focused on education and research, but are also places for community-building (Mulrooney & Kelly, 2020). The structural arrangement of universities impacts student learning and socialization and the "nature of the physical space on campus is not neutral, but can affect the extent to which students can form attachments with each other and academic staff" (Mulrooney & Kelly, 2020, p. 1).…”
Section: Institutional Context and Facilitators Of Inclusion And Belo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Those with disability were significantly more likely to agree that 'It is difficult to make friends at this institution' and 'I have very few friends or acquaintances at this institution that share my views and beliefs', and to significantly disagree with the statements 'I fit with other students at my university', 'There are other students at this institution who share my views and beliefs' and 'I can have quality interactions with other students' (see Table 3). We have previously shown that among higher education students, the nature of the physical space was important in enabling both a sense of belonging and social relationships to develop (Mulrooney & Kelly, 2020). Higher education establishments have invested in informal learning spaces to accommodate collaborative peer exchanges, but the extent to which such spaces are equally accessible and the potential for some students to be marginalised or excluded needs to be explored (Berman, 2020).…”
Section: General Belongingmentioning
confidence: 99%